EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING DEMI MENINGKATKAN KREATIVITAS SERTA KOLABORASI PADA SISWA SEKOLAH MENENGAH KEJURUAN - Nadila Nurul Aini; Muhammad Iqbal Alamsyah; Ivhan Afika Prila; Diella Amalia; Muhammad Dwikarama Zulis Fanda; Mohammad Wildan Habibi (STKIP Subang, 2026)
Vocational High Schools are expected to produce graduates who possess not only technical expertise but also important 21st-century competencies, particularly creativity and collaboration, in order to meet the demands of modern industries and the Industrial Revolution 4.0. However, the learning process in many vocational schools is still dominated by traditional teaching methods that often result in low student participation, limited initiative, and weak teamwork skills. This study aims to evaluate the effectiveness of Project-Based Learning (PjBL) in improving students’ creativity and collaborative abilities through a Systematic Literature Review approach. The study examines relevant national and international journal articles published between 2020 and 2025. The findings indicate that PjBL significantly enhances students’ creativity by engaging them in real-world projects that encourage idea exploration, problem-solving, divergent thinking, and the development of innovative products or solutions. In addition, PjBL effectively strengthens collaboration skills through group activities that require communication, shared responsibility, and negotiation among students. Although challenges such as limited learning facilities and the need to improve teachers’ competence in facilitating project-based activities still exist, PjBL remains a highly effective and relevant instructional model. Therefore, the study concludes that Project-Based Learning should be systematically integrated into vocational school curricula to better prepare students for the continuously evolving demands of the professional and industrial world.